Ditching Discovery-Creation for Unified Venture Creation Research. (March 2023) - Davidsson, Per
Extending earlier critiques, I suggest that continued use of Shanian discovery and Alvarez-Barnean creation views and their respective standpoints on "opportunities" would constrain future entrepreneurship research. Instead, I suggest venture creation be recognized as the field's true core, with or without the opportunity concept. Within a big tent of venture creation research, researchers with different knowledge interests and varying convictions regarding the roles of agency and structure in venture creation can partake in our most valuable contribution to the broader domain of economic and organizational studies: insights into the journey from non-existence to existence of new ventures.